Crustal study based on integrated geophysical techniques in the Northwestern Himalayas, Pakistan. Issue 4 (16th January 2023) - Hameed, Fahad; Khan, Muhammad Rustam; Dentith, Michael
Abstract : The present research aims to explicate the tectonics of the northwest Himalayas, Pakistan, based on integrated gravity, magnetic and earthquake data. The raw gravity and magnetic data were processed, and seven isoanomaly maps were prepared for qualitative interpretation, whereas a gravity model was prepared along the selected profile for quantitative interpretation. The local earthquake data have also been used to identify the various seismogenic layers in the subsurface and to understand how seismicity relates to regional structural features. Three northwest‐trending thick‐skinned blind basement faults are identified from the present study, namely the Indus Kohistan Seismic Zone (IKSZ), Bagh Basement Fault and Hazara Lower Seismic Zone. The IKSZ is the tectonically most active among them and responsible for the 2005 Kashmir earthquake (Mw = 7.6) and 1974 Pattan earthquake (Mw = 6.2) in the region. The present study also delineated the prominent location of the Main Central Thrust in which the high‐grade metamorphic rocks of Higher Himalayan Crystalline thrust over low‐grade metamorphic rocks of Lesser Himalayas along this thick‐skinned fault. The field evidence such as ductile deformation, zone of inverted metamorphism, and brittle deformation also confirm this location. The sharp bending of the crystalline crust, as well as deep basement just south of Kohistan Island Arc (KIA), indicate that the high density and susceptibility rocks of this arc thrust on the leading margin of the Indian Plate along the Main Mantle Thrust. This thrust fault is a major suture zone separating the KIA in the north from the Indian Plate in the south. The other faults in the region exist in the sedimentary/meta‐sedimentary wedge and are thin‐skinned. It is inferred from the current investigation that the study area exhibits a composite style of deformation. Moreover, the gravity model combined with earthquake data suggested the existence of multiple décollement zones below the Hazara‐Kashmir Syntaxis. The model envisaged an increase in the thickness of the Indian Plate continental crust in the northeast direction. Abstract : This study discriminated between the thin‐skinned and thick‐skinned structural features and indicated the crustal thickness in the Northwestern Himalayas, Pakistan based on integrated gravity, magnetic, and earthquake data.